Doing management research : a comprehensive guide - Thiétart, Raymond Alain (Online access: SAGE SAGE Research Methods Core., 2001)
Doing Management Research, a major new textbook, provides answers to questions and problems which researchers invariably encounter when embarking on management research, be it quantitative or qualitative. This book will carefully guide the reader through the research process from beginning to end.